Vacuum Drying Kinetics of Barbunya Bean (Phaseolus vulgaris L. elipticus Mart.) - Kayisoglu, Serap (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
Vacuum drying characteristics of barbunya bean (P. vulgaris L. elipticus Mart) were investigated in a laboratory scale vacuum dryer for a temperature range of 50-80 °C at constant vacuum pressure of 50 kPa. Results indicated that drying took place in the falling rate period. Six mathematical models were fitted to the experimental data; these were the Newton, Page, Henderson and Pabis, Logarithmic, Wang and Singh, and approximation of diffusion models. Comparison of the coefficient of determination (R 2), root mean square error (RMSE) and reduced chi-square (x 2) between the observed and the predicted moisture ratios showed that the Logarithmic model gave the best results for describing single layer drying of barbunya beans. The effect of temperature on Logarithmic model constants and coefficients were also evaluated. Moisture transfer from barbunya was described by applying the Fick's diffusion model and the effective diffusivity was calculated. Effective diffusivity increased with increasing temperature. An Arrhenius relation with an activation energy value of 14.73 kJ mol -1 expressed the effect of temperature on the diffusivity.